Les investisseurs institutionnels et le marché boursier

(untitled) (HEC Montréal, 1982)
The size and number of private Canadian financial intermediaries have grown sharply since 1930. In that year, life insurance companies and chartered banks controlled over 70% of the assets of private Canadian financial intermediaries. By 1980, chartered banks were still dominating over other intermediaries but life insurance companies were smaller by assets than other pension funds or trust and mortgage loan companies. Public intermediaries have grown significantly also. The rise of pension funds has been a boon to the stock market in that it is where they invested a larger proportion of their rapidly growing assets than other intermediaries. The overall investment pattern of these intermediaries in the fast twenty years has been to invest less in bonds and more in assets that reflect their main line of business. They also invested in other assets such as mortgage loans in the case of life insurance companies and slightly more in the stock market. Life insurance companies have experienced rapid growth since 1930, but their rate of growth has slowed. This may be attributed to the mature state of the insurance market and to the emergence of group insurance, a form of insurance that carries less premiums as a percent of life insurance in force than does ordinary insurance. Investment income has played an increasingly important part of the income of life insurance companies over the fast fifty years. The investment pattern of life insurance companies has varied over the years. Public bonds reached their zenith during World War II, declining continuously since then, having been replaced by corporate bonds. Equity investments have represented a relatively constant proportion of life insurance investments. However, after the netting out of Sun Life's unusually high equity investments in the 1930's, sharp changes took place within the equity portfolio. Preferred shares rose from insignificance to being roughly equal to investments in common shares in the 1946-1951 period. Since 1951, investment in preferred share has declined constantly despite a minor resurgence in the fast few years. The Canadian stock market exchanges showed erratic secular growth in the 1930-1955 period. Since then, the pattern has been positive despite the odd negative years.